"Stop Bullying No Fear Seminar" at SMP IP Darut Taqwa Dusun 09 Karang Anyar Village Labuhan Maringgai - Habib Ismail; Abid Assidiqi Zahra; Cindy Eka R.; Eva Ainur Rizqi; Eva Yuniarti; Irsyad Syafe’i (Ihsanniat: Jurnal Pengabdian Kepada Masyarakat, 2025)
The seminar “Stop Bullying No Fear” at SMP IP Darut Taqwa, Dusun 09, Karang Anyar Village, Labuhan Maringgai Regency. Aims to raise students’ awareness and understanding of the negative impacts of bullying and prevention strategies. This event involves all school components, including teachers, students, and parents, in an effort to create a safe and bullying-free learning environment.The method used in this seminar is a participatory approach, where participants are actively engaged through interactive discussions, educational video screenings, and bullying situation simulations. This approach is designed to help students understand various forms of bullying, such as physical, verbal, social, and cyberbullying, as well as their long-term effects on victims.The results of this seminar show a significant improvement in students’ understanding of bullying. Students are more capable of identifying bullying actions and understanding their crucial role in preventing and responding to such situations. Additionally, the seminar encourages the development of an inclusive and respectful school culture, where every individual feels safe and valued.The active participation of all school elements in this seminar is expected to foster a collective commitment to eradicating bullying. Thus, SMP IP Darut Taqwa can serve as a model for other schools in creating an educational environment free from bullying, supporting students’ positive development.